2006
DOI: 10.1002/cncr.21668
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II study of two opposite administration sequences of irinotecan and cisplatin in patients with advanced nonsmall cell lung carcinoma

Abstract: A novel method to simultaneously measure liquid solid mass transfer and external wetting efficiency was employed at column to particle ratios of 10, 6 and 3. Two prewetting procedures representing the upper (Kan) and lower (Levec) hysteresis branches were used. For a multipoint distributor on a Kan prewetted bed wetting efficiency and the specific mass transfer coefficient were almost unaffected by column diameter. The multipoint distributor on a Levec prewetted bed exhibited a decrease in specific mass transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 62 publications
1
34
0
Order By: Relevance
“…Using the concurrent cisplatin and irinotecan administration schedule, we showed objective tumor responses in 47% of chemo-naive NSCLC patients with 1-year survival rate of 63.3%. 14 In the current study, 40.6% of patients with previously treated NSCLC responded to the second-line irinotecan and cisplatin therapy, which is quite comparable to our first-line response rate and also the results of other trials wherein the irinotecan and cisplatin regimen was used in a front-line setting (Table 7).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Using the concurrent cisplatin and irinotecan administration schedule, we showed objective tumor responses in 47% of chemo-naive NSCLC patients with 1-year survival rate of 63.3%. 14 In the current study, 40.6% of patients with previously treated NSCLC responded to the second-line irinotecan and cisplatin therapy, which is quite comparable to our first-line response rate and also the results of other trials wherein the irinotecan and cisplatin regimen was used in a front-line setting (Table 7).…”
Section: Discussionsupporting
confidence: 87%
“…10 When given together with cisplatin, which has a different toxicity profile, irinotecan showed synergistic antitumor effect in vitro and significant antitumor activity in the firstline setting, as summarized in Table 7. 7,[11][12][13][14] In a second-line setting, however, 2 Japanese studies showed conflicting results on its activity against NSCLC. 15,16 Negoro et al treated 26 previously treated NSCLC patients with 100 mg irinotecan/m 2 every week and observed no response while they reported a 34% response rate in chemotherapy-naive patients in the same study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eligibility of study subjects were described in detail elsewhere [10], and should have adequate hepatic and renal functions defined as, serum bilirubin level ≤1.5 times, and aspartate aminotransferase (AST) and alanine aminotransferase (ALT) ≤2.5 times the upper limit (UNL) of the institutional reference range, and serum creatinine ≤1.5 mg/dl. Table 1 shows their characteristics.…”
Section: Subjects and Treatmentmentioning
confidence: 99%
“…This study subjects were described in detail elsewhere [12]. Treatment consisted of irinotecan 80 mg/m 2 i.v.…”
Section: Study Population and Sample Collectionmentioning
confidence: 99%